ダイ38ジ ナンキョク チイキ カンソクタイ チガク ブモン ノ ヤガイ カンソク ニ オケル チキュウ ブツリガク テキ ケンキュウ (1996-1998) - 金尾, 政紀; カナオ, マサキ; 東, 敏博; ヒガシ, トシヒロ; Kanao, Masaki; Higashi, Toshihiro (1999)
P(論文) 第38次日本南極地域観測隊(1997年度)の地学研究部門において, 野外における地球物理学的観測をいくつか実施した。その主たる目的は, リュツォ・ホルム湾地域の地殻および上部マントル(いわゆるリソスフェア)の構造と進化過程を, 地震学的・測地学的手法を中心に研究することである。沿岸露岩域では, 湾周辺の地殻構造を面的に調べるために, 可搬型の広帯域地震計および短周期地震計を複数台設置して, 記録される遠地地震波形を解析した。また, 可搬式重力計による測定で得られたブーゲ異常により, 宗谷海岸に沿ってのモホ面の深さ分布を推定した。さらに, 沿岸露岩調査や内陸旅行においてGPS観測を行い, これまで特にデータの少ない内陸のみずほ基地からドームふじ観測拠点間の測定により, 南極大陸内陸部の氷床の流動と地殻構造の推定にとって貴重なデータを得た。一方, 第38次隊より実施中の「東南極リソスフェアの構造と進化の研究計画(SEAL計画)」の一環として, 氷床上での短周期地震計によるアレイ観測, スチーム式ボーリング装置の掘削試験, 投下式地震計(ペネトレーター)の無線試験, 長寿命電池の電圧降下試験等の, 短周期地震波による地殻構造探査と機器類の諸試験を行った。これは将来の構造探査において使用することを前提に機器の開発を重ねると共に, アレイ観測データの波形の相関を調べること等をして氷床上での波動伝播特性を研究する。また, 過去の屈折法探査データの反射法的処理から得られている下部地殻における反射層の一部を検出し, みずほ高原の地殻構造を詳細に探ることも目的とする。 Several geophysical field research observations and geodesic surveys were conducted during the wintering season of the 38th Japanese Antarctic Research Expedition (JARE-38) in 1996-1998. Lithospheric structure and evolution of the Lutzow-Holm Bay region, East Antarctica were obtained from continuous observations by portable broadband seismographs and from gravity surveys on outcrops around the Soya Coast region. Several GPS measurements both on the outcrops along the Soya Coast and on the ice sheet from the coastal area near Syowa Station to the inland of Dome Fuji Station area will give information on crustal uplift due to glacial rebound, on mass reduction and surface movement of the continental ice sheet, and on crustal thickness up to the Dome Fuji Station area. Moreover, some test measurements concerning the seismic refraction/reflection experiments by the SEAL (Structure and Evolution of the East Antarctic Lithosphere) project were carried out in the JARE-38 wintering season. Such instruments as a steam water ejective-type ice/snow-drilling system, an expendable ground system segment (GSS), and long term batteries were repeatedly tested to determine whether they operate properly in Antarctic meteorological conditions. Additionally, seismic array observations using short period seismometers on the ice sheet were conducted ...